Inovasi Diversifikasi Olahan Hasil Laut Pada Siswa Sekolah Menengah Kejuruan Maritim Cirebon - Novianti, Teni (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2023)
Cirebon Maritime Vocational High School is one of the vocational schools in the field of fisheries and maritime affairs. According to the results of observations made by researchers, the fundamental problem is that the results of student practice are still limited to fish-based preparations and there is no label on the product packaging. The purpose of this study is to determine the level of knowledge and skills of students in innovating the diversification of seafood processed processed frozen at SMK Maritime Cirebon. The research method was carried out by means of participatory training involving 18 students of the Fisheries Product Processing Technology study program for Class XII of Cirebon Maritime Vocational School as many as 18 who would take part in preparation for the skills competency exam. Through innovation activities and diversification of marine products can increase students' knowledge and skills on frozen breaded shrimp processed products. There was an increase in the aspect of knowledge of 42.47% and an increase in the aspect of students' skills regarding the diversification of processed frozen shrimp reaching 68.7% with the criteria of being skilled as many as 11 respondents (61.11%) and the criteria quite skilled as many as 7 respondents (38.89%).